Fault Diagnosis in Static Converters Used in Induction Heating Systems - Ouahiba Fadli; Mohamed Lokmane Bendaas; Rachid Abdessemed (Institute of Advanced Engineering and Science, 2018)
This paper presents different techniques on fault diagnosis in static converters used to supply and control induction heating systems. These techniques allow the detection and the location of the failed semiconductor switches. After an overview of the device with its main features in healthy state, we have afterwards focused on the fault detection and diagnosis in three electronic power converters which constitute the power generator of the induction furnace. For uncontrolled three-phase rectifier, three external methods based on the analysis of lines currents are used: Average currents method, Current space vector trajectory, called Current Park’s vector approach and Spectrum analysis. For the buck converter (chopper), analytic redundancy approach, based on the residues calculation, is used. For the series resonant inverter, a simple and efficient method based on the average voltages analysis, allows the detection and the location of the power switch in fault. The obtained simulation results, in Matlab/Simulink, are presented and discussed. They reveal that the proposed diagnostic techniques are of great interest.